Isolation and Identification of Turmeric Rhizome Endophytic Bacteria (Curcuma longa L.) Using the 16s rRNA Method - Anggraeni, Vina Juliana; Fatmawati, Fenti; Khofiyah, Ikma Nidaul (Jurnal Agrotek Ummat, 2024)
Turmeric (Curcuma longa L.), is one of the components of traditional medicine. Oleoresin, curcumin, resin, essential oils, desmetoxycurcumin, and bidesmetoxic curcumin are secondary metabolite compounds found in turmeric rhizomes. The aim of this research is to obtain pure isolates and identify specific bacterial species using Gram staining and 16S rRNA methods which are expected to be used as raw materials for new drugs. The hypothesis of this research is that isolates and species of endophytic bacteria were obtained from turmeric rhizomes (Curcuma longa L.). The methods used include material preparation, sample preparation and sterilization, bacterial isolation, DNA isolation, and sequencing. Seven isolates of turmeric rhizome bacteria (Curcuma longa L.) were obtained and the results of molecular identification were carried out on 1 isolate using the 16S rRNA method with code BE.K.5, which is homologous/has 94% similarity to Lysinibacilus sphaericus